Cover Picture: The Chemical Basis of Fungal Bioluminescence (Angew. Chem. Int. Ed. 28/2015). Issue 28 (12th June 2015) - Purtov, Konstantin V.; Petushkov, Valentin N.; Baranov, Mikhail S.; Mineev, Konstantin S.; Rodionova, Natalja S.; Kaskova, Zinaida M.; Tsarkova, Aleksandra S.; Petunin, Alexei I.; Bondar, Vladimir S.; Rodicheva, Emma K.; Medvedeva, Svetlana E.; Oba, Yuichi; et al.
<x xml:space="preserve">Abstract</x> Glowing fungi were described by Aristotle as early as the fourth century B.C. In their Communication on page 8124 ff., I. V. Yampolsky, J. I. Gitelson, and co‐workers unveil the structure of fungal luciferin, a compound that is responsible for fungal biolumescence.